Survey of Hermite Interpolating Polynomials for the Solution of Differential Equations - Kumari, Archna; Kukreja, Vijay K. (Mathematics (Basel), 2023)
With progress on both the theoretical and the computational fronts, the use of Hermite interpolation for mathematical modeling has become an established tool in applied science. This article aims to provide an overview of the most widely used Hermite interpolating polynomials and their implementation in various algorithms to solve different types of differential equations, which have important applications in different areas of science and engineering. The Hermite interpolating polynomials, their generalization, properties, and applications are provided in this article.